The links between suicidal behaviour and endorsement of myths about suicide in young people - Strukcinskienė, Birute; Strukcinskaite, Vaiva; Rauckiene-Michaelsson, Alona (Social Welfare: Interdisciplinary Approach, 2019)
For many years in Lithuania the rate of suicide mortality has been remarkable in magnitude, especially in the young population. Social and public health determinants, risk behaviour issues, prevention and control of suicide in teenagers and young people needs urgent attention. The aim of the study was to investigate the self-reported perception of young people - the university students concerning suicide, the myths and reality on this phenomenon, and the links between suicidal behaviour and endorsement of myths about suicide. The self-reported survey was conducted in the university settings. The results of the survey showed that young people lack knowledge about the phenomenon of suicide and suicidal behaviour, and they still believe myths about suicide. The study revealed that one-fifth of young people had suicidal thoughts, and boys along with urban residents and suicidal family were at higher risk. Half of the students surveyed self-reported suicidal peers in their environment. Young people lack knowledge on suicide prevention, and preventive events. The study revealed that raising awareness, obtaining knowledge, and providing information to young people on the phenomenon of suicide, suicidal behaviour, and warning signs of possible attempt and suicide risk are the priority issues. Suicide prevention activities on individual, community, local and national levels need to be addressed.